Pengaruh Sambaran Petir Langsung pada Variasi Ketinggian Menara Vertikal terhadap Tegangan Induksi yang Dirasakan oleh Jaringan Distribusi Disekitarnya - Budi Utama (Faculty of Engineering, Universitas Gadjah Mada, 2007)
If the top of telecommunication towers or radio or television have been struck by a lightning, distribution lines in the vicinity of those would immediately underwent an induced overvoltage impuls. Magnitude of the induced voltage impuls depend on how tall the tower above ground. Such lightning stroke is type of an indirect lightning stroke which is always appear in the problem of the induced overvoltage phenomenon on overhead distribution lines. Examinant of the effects of various height of the tower and the distance parameter between the tower and the route of distribution line on rate of rise of the induced voltage of the lightning is undertaken in this paper, and the computer is as its simulator. The method of the simulation of a lightning stroke in the vicinity of distribution line and its formulation is adopted from a simulation model that has been_ proposed by Ishii et al. (1994) and Eriksson et al (1982) respectively. The result of the simulation show that presence of a vertical tower structure in the vicinity of the distribution line route will result in a lower induced voltage (on the order of 13.4 %), and effect of tower height parameter is very significant for the assumed conditions. It is proposed that this significant parameter be studied extensively in order to predict the induced voltage accurately.